In vitro regeneration from cotyledons of watermelon - Zarka, V.; Velich, L.; Bisztray, Gy. (International Journal of Horticultural Science, 2000)
Cotyledonary segments of five different genotypes of watermelon were used to induce organogenesis. Five different hormone combinations were applied to enhance the induction of shoot formation on the surface of the segments. The phases of organogenesis were followed with light and scanning electron microscope. Shoots were obtained after four weeks, then the shoots were transferred to hormone free medium for root induction.This method of regeneration can be applied in transformation experiments. GUS histochemical assay was made to check the expected success of using Agrobacterium for the transformation.